Ответы 2

  • 2*cos(\frac{x}{2}\ - \frac{\pi}{2}\ )=\sqrt{3} \\ cos(\frac{x}{2}\ - \frac{\pi}{2}\ )=\frac{\sqrt{3} }{2} \\ \frac{x}{2}\ - \frac{\pi}{2}=\frac{\pi}{6} \ \frac{x}{2}=\frac{4\pi}{6} \ x=\frac{8\pi}{6}=\frac{4\pi}{3}+2\pi*n

  • 2cos(\frac{x}{2} - \frac{\pi}{6})\sqrt{3}

    cos(\frac{x}{2} - \frac{\pi}{6})\frac{\sqrt{3}}{2}

    \frac{x}{2} - \frac{\pi}{6} = \frac{\pi}{6}

    \frac{x}{2} = \frac{\pi}{3}

    x = \frac{\pi}{3} +2\pi n

  • Добавить свой ответ

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years